Penggunaan Metode MFEP Dalam Menentukan Jenis Daging Ayam Yang Berkualitas Untuk Di Konsumsi Berbasis Web - Fransiska, Yunita; Irvan, Irvan; Lubis, Fachrul Rozi (Universitas Islam Negeri Sumatera Utara, 2022)
Chicken meat is an ingredient that contains high animal protein where many of the chickens also make a major contribution to meeting the animal protein needs of the Indonesian people. The need for chicken meat has increased every year, because the price is affordable by all people. There are many types of chicken meat that are widely circulated among the Indonesian people, plus so far there is no information about chicken meat that is suitable for consumption. The community must be required to be more careful in choosing chicken meat that is suitable for consumption. The purpose of this research is to determine which meat is suitable for consumption by the community by using the MEFP method as an indicator in the calculation of the assessment with the results of being able to determine chicken meat that is suitable for consumption. The criteria used in this study are color, aroma, texture, price, and protein with the results of probiotic and prebiotic chickens as chickens that have good value for consumption Keywords: Chicken Meat, Mefp